Time‐dependent dynamical Bragg diffraction in deformed crystals by the beam propagation method. Issue 6 (23rd September 2022) - Krzywinski, Jacek; Halavanau, Aliaksei
Abstract : A novel method is presented of simulating dynamic diffraction in distorted crystals using a fast Fourier transform based beam propagation approach. Abstract : This paper describes how to efficiently solve time‐dependent X‐ray dynamic diffraction problems in distorted crystals with a fast Fourier transform based beam propagation method. Examples are given of using the technique to simulate the propagation of X‐ray beams in deformed crystals in space and time domains relevant to the cavity‐based X‐ray free‐electron lasers and X‐ray free‐electron laser self‐seeding systems.